SIX DIMENSION STRATEGY AS A BASIS OF BANKING STANDARD CONTRACT - Frederik, Wulanmas (UI Scholars Hub, 2012)
Indonesia banking based on Article 4 of Act No.10, 1998, aims at supporting the implementation of national development in order to improve equity, economic growth and national stability in the direction of improving people’s welfare. Therefore, to show how important is banking role in supporting the implementation of development, the 6 (six) Strategic Dimensions as the foundation of Banking Standards Contract are: (1). Prudent Banking Supervision and Good Corporate Governance (GCG) in banking activities, (2). Refunctionalization the principle of Contract Law in Banking Standards Contract, (3). Ethics Value in Business, (4). The Act No. 8, 1999 on Consumer Protection, (5). Enforcement of Human Rights Principles in banking activities, (6). Abuse of Circumstances implementations (Misbruik van Omstandigheden) in banking Contract. Based on the 6 (six) Strategic Dimension as the foundation of Banking Standard Contract, it will undoubtedly create justice, equity and assurance of the rights and obligations of the parties framed in the contractual and law bonds.